Chemical Profile and Observing Honey Adulteration Using Fourier Transform Infrared (FTIR) Spectroscopy and Multivariate Calibration - Sulistyo Prabowo; Yudha Agus Prayitno; Yuliani (Journal of Food and Pharmaceutical Sciences, 2020)
Honey is a complex mixture that contains nutrients and bioactive composition and chemical compositionthat is needed by the human body. Honey is also rich in antioxidants because it is prone to falsification given its manyproperties. This study discusses the chemical and nutritional profiles and the observation of counterfeiting in honey usingthe infrared septicroscopy method. The honey used is obtained from providers of native honey from Kalimantan forestswith 3 kinds of honey brands, namely Mahuka A (MHA), Mahuka B (MHB) and Mahuka C (MHC). Tests of chemicaland nutritional profiles included Water content, ash content, protein content, fat content and calcium levels followed byhoney counterfeiting observation using the Fourier Transform Infrared (FTIR) method with a combination of Partial leastsquare (PLS) calibration model and Principle Component Regression (PCR). The results of all honey samples havevarying values in the water content between 26.75 - 31.00%. Ash content of 0.10 -0.16%. Protein content 0.24 - 0.88%fat content 0.08 -0.44% carbohydrate content. Observation of FTIR honey counterfeiting is used to replace the authenticity of Honey (MH). FTIR combined with Partial Least Square (PLS) was optimized in the subsequent testing ofa mixture of sucrose (MCS) with native honey (MH). Calibration models were taken in a combination of regions 1423 -1825 cm-1. A high coefficient of determination (R2) of 0.9960 with a calibration value (RMSEC) of the root error of thesquare root low of 0.0898% v / v was successfully understood in the MHA on the PLS model. high R2 values and lowRMSEC and RMSEP values on calibration and validation assessments with both accuracy and precision models used.